2016
DOI: 10.1016/j.kint.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

The costimulatory receptor B7-1 is not induced in injured podocytes

Abstract: Recent research on podocytes has proposed B7-1 as an important player in podocyte biology and as a potential new therapeutic target. B7-1 was upregulated in injured podocytes and described as a biomarker to identify patients who may benefit from abatacept, a B7-1 blocker. However, after this initial enthusiasm, several reports have not confirmed the efficiency of abatacept at inducing proteinuria remission in patients. In order to resolve these discrepancies, we explored the role of B7-1 in the injured podocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…Yu et al showed the resolution of nephrotic range proteinuria after B7-1 inhibition with Abatacept (CTLA-4–Ig) treatment in patients with rituximab-resistant recurrent FSGS and in patients with glucocorticoid-resistant primary FSGS ( 18 ), suggesting that B7-1 can be a target for the treatment of proteinuria. However, these findings have recently been challenged by Baye et al ( 19 ). These new observations led us to explore the possible role of B7-1 in febrile children.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al showed the resolution of nephrotic range proteinuria after B7-1 inhibition with Abatacept (CTLA-4–Ig) treatment in patients with rituximab-resistant recurrent FSGS and in patients with glucocorticoid-resistant primary FSGS ( 18 ), suggesting that B7-1 can be a target for the treatment of proteinuria. However, these findings have recently been challenged by Baye et al ( 19 ). These new observations led us to explore the possible role of B7-1 in febrile children.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that B7-1 was expressed on podocytes of lupus nephritis (LN) (Reiser et al 2004), and the expression of podocyte B7-1 in LN patients and LN mouse models is positively correlated with the degree of proteinuria. However, new evidence has stricken up a discordant tune (Baye et al 2016), leading to further mandatory studies of the application of B7-1 blockers in treating proteinuric patients (Novelli et al 2016a).…”
Section: Costimulatory Factorsmentioning
confidence: 99%
“…Moreover B7-1 (CD80), which is usually expressed on B cells and APCs and induces T-cell co-stimulation, has also been detected on podocytes in several models of proteinuric kidney diseases, including LN [76]. However, recent studies have reported conflicting results suggesting that B7-1 is not expressed in mouse models of LN and in human LN [77,78]. Moreover, clinical trials in patients with LN failed to demonstrate a clear outcome benefit of abatacept, an inhibitor of B7-1/CD28 interaction [79,80].…”
Section: Podocytes As Immune Cellsmentioning
confidence: 99%